Letter from Lieutenant Commander J. D. Marvin to James Curtis Booth, January 12, 1872 - Marvin, J. D. (1872)
Lieutenant Commander J. D. Marvin consults with James Curtis Booth (1810-1888) about the use of silver or copper in ordinance experiments at DuPont’s Powder Mill. Booth notes on the letter "Silver disks advised of 999 1/2 fine."
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; E.I. du Pont de Nemours & Company; Marvin, J. D.